Analysis Of Competence And Work Discipline On Employee Performance With Job Satisfaction As A Mediating Variable At The Regional Office Directorate General Of Treasury North Sumatra Province - Ellisa Fitriani; Sri Rahayu; Mesra B (Jurnal Fokus Manajemen, 2026)
Employee performance is a strategic factor in supporting the effectiveness of government tasks, especially in vertical agencies of the Ministry of Finance such as the Regional Office of the Directorate General of Treasury (Kanwil DJPb) of North Sumatra Province. This study aims to analyze the effect of competence and work discipline on employee performance with job satisfaction as a mediating variable. This study uses a quantitative approach with a survey method. The population in this study was all 70 employees of the Regional Office of the Directorate General of Treasury in North Sumatra Province, with a saturated sample technique used for sampling. Primary data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results showed that competence and work discipline had a positive and significant effect on employee performance. In addition, competence and work discipline also had a positive and significant effect on job satisfaction. Job satisfaction was found to have a positive and significant effect on employee performance and acted as a mediating variable in the relationship between competence and employee performance, as well as between work discipline and employee performance. The coefficient of determination showed that competence and work discipline were able to explain 53.8% of the variation in job satisfaction, while competence, work discipline, and job satisfaction were able to explain 63.4% of the variation in employee performance. The results of this study imply that improving competence, enforcing consistent work discipline, and managing job satisfaction in a sustainable manner are important factors in improving employee performance in the North Sumatra Provincial Office of the Directorate General of Taxes.